PROPOSAL FOR AN UNIFORM DATA STANDARD FOR ICHNOLOGICAL 3D TRACKING AND POST-PROCESSING - MARCO PETRUZZELLI; NOVELLA RAZZOLINI; RUGGERO FRANCESCANGELI (Rivista Italiana di Paleontologia e Stratigrafia, 2011)
Vertebrate fossil tracks have been studied through 3D modelling techniques during the last two decades to improve tracking procedures. Different laser scanners and software have been used during field investigation and this differentiation caused incompatibility between many analysis programs. Post processing procedures are not standardized among scientists and file precision give different results in additionally constrain comparison. The starting point to find a solution to the problem is to point out the main technologies used to collect data in the field. The resulting protocol does not oblige to uniform hardware but it does suggest combining different laser scanners with a minimum post processing to optimize the result. Important inkling would be to use 2D relief as a reference to organize 3D tracking procedures. Saving formats during post processing are improved by setting fixed landmarks integrated in the 3D model in a multitask file. The D.I.C.O.M. medical standard (*.cdm format) and the 3D printing international standard (*.stl format) when combined, may be a good solution for uniform the format. This approach might be the first step for the standardization of source and derived files and the creation of a worldwide 3D ichnological catalogue. This will allow creating a scientific improvement in terms of reproducibility and comparison of the experience.